2006
DOI: 10.1164/rccm.200509-1477oc
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for Advanced Glycation End-Products Is a Marker of Type I Cell Injury in Acute Lung Injury

Abstract: Rationale: Receptor for advanced glycation end-products (RAGE) is one of the alveolar type I cell-associated proteins in the lung. Objectives: To test the hypothesis that RAGE is a marker of alveolar epithelial type I cell injury. Methods: Rats were instilled intratracheally with 10 mg/kg lipopolysaccharide or hydrochloric acid. RAGE levels were measured in the bronchoalveolar lavage (BAL) and serum in the rats and in the pulmonary edema fluid and plasma from patients with acute lung injury (ALI; n ϭ 22) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
402
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 412 publications
(432 citation statements)
references
References 44 publications
23
402
2
5
Order By: Relevance
“…sRAGE has been indicated to be involved in infl ammatory processes in several ways. First, sRAGE blood concentrations are associated with various infl ammatory diseases in patients and in rats with experimentally induced ALI [29]. Further more, it is suggested that sRAGE can compete with full length cell-surface RAGE for ligand engagement, preventing these ligands from binding to RAGE or other receptors and/or exerting eff ects otherwise.…”
Section: Soluble Rage (Srage)mentioning
confidence: 99%
See 4 more Smart Citations
“…sRAGE has been indicated to be involved in infl ammatory processes in several ways. First, sRAGE blood concentrations are associated with various infl ammatory diseases in patients and in rats with experimentally induced ALI [29]. Further more, it is suggested that sRAGE can compete with full length cell-surface RAGE for ligand engagement, preventing these ligands from binding to RAGE or other receptors and/or exerting eff ects otherwise.…”
Section: Soluble Rage (Srage)mentioning
confidence: 99%
“…Th e involvement of sRAGE during infection is not known. Based on experimental studies in rats and in patients with ALI, sRAGE has been described as a marker of lung injury [29].…”
Section: Soluble Rage (Srage)mentioning
confidence: 99%
See 3 more Smart Citations